Value of Quantitative Intraoperative Electrocorticography During Anterior Temporal Lobectomy in Temporal Lobe Epilepsy Patients - Sebaei, Dina; Eldin, Ali M. Salah; Hussein, Samar M.; Abogresha, Noha M.; El-Baz, Amani (South Eastern European Journal of Public Health, 2024)
Introduction: There is debate on the predictive usefulness of electrocorticography (ECoG) during anterior temporal lobectomy (ATL) in temporal lobe epilepsy (TLE) patients. The purpose of this study was to determine the usefulness of quantitative intraoperative ECoG monitoring for postoperative seizure outcomes after ATL in TLE patients. Methods: The study enrolled thirteen TLE patients who underwent ECoG-assisted ATL. Pre- and post-resection ECoG spike frequency (/min) and spike amplitude (μv/mm) were analyzed with histopathological and preoperative video-electroencephalography (EEG) data. After one year of follow-up, patients were classified as seizure-free (Engel Class I) or with residual seizure outcomes using the Engel Seizure Outcome Classification Scheme. Results: The pre-resection and post-resection ECoG showed significant differences in spike frequency (/min) and amplitude (μv/mm) (P-value < 0.001). Patients with residual seizures (15.4%) showed significantly greater pre- and post-resection ECoG spike frequency and amplitude, as well as significantly higher seizure frequency before surgery, compared to patients with postoperative seizure freedom (84.6%). The pre-resection ECoG spike frequency was significantly greater in TLE patients with histopathology focal cortical dysplasia (FCD) than in those with non-FCD. The post-resection ECoG revealed a sensitivity of 100%, a specificity of 50%, a negative predictive value of 100%, and a positive predictive value of 91.67%. Conclusions: Pre-resection ECoG spike frequency and amplitude can be used as a predictive tool for postoperative seizure outcomes, particularly when video-EEG can't identify the epileptogenic zone (EZ) in TLE patients undergoing ATL.